Main Complications during Pregnancy and Recommendations for Adequate Antenatal Care in Sickle Cell Disease: A Literature Review - Figueira,Camilla Olivares (2022)
Abstract Sickle cell disease (SCD) is the most common monogenic disease worldwide, with a variable prevalence in each continent. A single nucleotide substitution leads to an amino-acid change in the β-globin chain, altering the normal structure of hemoglobin, which is then called hemoglobin S inherited in homozygosity (HbSS) or double heterozygosity (HbSC, HbSβ), and leads to chronic hemolysis, vaso-occlusion, inflammation, and endothelium activation. Pregnant women with SCD are at a higher risk of developing maternal and perinatal complications. We performed a narrative review of the literature considering SCD and pregnancy, the main clinical and obstetrical complications, the specific antenatal care, and the follow-up for maternal and fetal surveillance. Pregnant women with SCD are at a higher risk of developing clinical and obstetric complications such as pain episodes, pulmonary complications, infections, thromboembolic events, preeclampsia, and maternal death. Their newborns are also at an increased risk of developing neonatal complications: fetal growth restriction, preterm birth, stillbirth. Severe complications can occur in patients of any genotype. We concluded that SCD is a high-risk condition that increases maternal and perinatal morbidity and mortality. A multidisciplinary approach during pregnancy and the postpartum period is key to adequately diagnose and treat complications.